Reduction of warpage occurrence on stack-die QFN using FEA and statistical method - Abdullah I.; Ahmad I.; Talib M.Z.M.; Kamarudin M.N.B.C. (2023)
Warpage is greatly affected by package geometries, such as dimension of matrix array, pad, die and passive components as well as molding compound properties. It is also related to thermal mismatch i.e. coefficient of thermal expansion (CTE) and reliability of passive components in the package. So in order to reduce warpage occurrence in all packages, it is proposed that the combination of CTE properties of QFN packages layer need to be optimized. This study used finite element method (FEM) to perform extensive structural analysis of QFN package designs with respect to different combination of thermal properties and the possible occurrence of warpage. The results obtained were then verified with experimental data. The FEA method was able to simulate the warpage occurrence and the statistical method was able to identify the optimal combination of thermal properties of the layers. It was also found that the optimum combination of CTE properties will reduce the probability of the warpage occurrence.